Paradigma baru fiqih perdagangan bebas: Dialektika ulum al-din dan hukum negara - Akmal Bashori (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
The people of the world (Muslim) enter a new era where between free countries do trade relations without any customs duties, this is called free trade. Everything is governed by market players who have strong capital, rooted in the concept of capitalism. Although Islam advocates seeking as much treasure as you live forever, however, Islam does care about each other. With the advent of free trade, what should the Indonesian state do? Do you have to sacrifice the withdrawal of customs levy which has been the country's income? How does Islam see this? What is the concept that offer fiqih about free trade? The key problem must be between the science of religion with the state so that the policies taken by the state bring maslahat to millions of Indonesian people.